Training physiotherapy students in basic wheelchair provision. Experiences at two universities in Colombia. - Velasco Forero, Sandra Esperanza; Arias Becerra, Nidia Johana; Torres Narváez, Martha Rocío; Mondragón Barrera, Mónica Alejandra; Munera Orozco, Sara; Goldberg, Mary; Kandavel, Krithika; Esquivel Ortiz, Paola Rocio (Disability & Rehabilitation: Assistive Technology, 2024)
Wheelchair provision training is essential to overcome barriers related to the lack of knowledge of health professionals on this topic. Appropriate knowledge of the service provision process may lead to higher quality service and products, and thus be more likely to help people with mobility impairments achieve the fundamental human right of personal mobility. This study aimed to describe a training intervention for two groups of future physiotherapists in Colombia, assess cohort differences in performance on a knowledge test, and explore their post-training perceptions. A quantitative retrospective study with a historical, descriptive-comparative design was conducted. 525 sixth-semester participants completed the International Society of Wheelchair Professionals Wheelchair Service Provision – Basic Test online in Spanish after curriculum modifications were implemented. The test assesses knowledge in seven domains: Assessment; Prescription; Products; Fitting; User training; Follow-up, maintenance, and repairs; and Process. The training intervention was successfully implemented with Physiotherapy students from two institutions, resulting in a 57% increase in test approval rates. Participants demonstrated increased knowledge, satisfaction with the course content, and application of learning to their current work. These results suggest implications for what pedagogical approach to employ, when curricular change may be warranted, and specific considerations for the Colombian context. Furthermore, identifying the minimal knowledge basis for undergraduate programs and facilitating its dissemination can support interprofessional education and enhance professionals' capacity to support wheelchair provision services. IMPLICATIONS FOR REHABILITATION: Developing pedagogical materials and resources should address academic needs while also being adaptable to the healthcare system and cultural and economic resources. Establishing minimal knowledge bases for physiotherapists and facilitating their dissemination to support interprofessional education are crucial steps. Sharing pedagogical experiences that improve health workforce training promotes the quality of wheelchair service provision, benefiting the functional independence and well-being of people with disabilities. The use of international resources such as the ISWP test in the training of the health workforce contributes to the standardization of the training process regardless of the context.